PATTERNS OF CLINICAL MEDICO-LEGAL CASES: A RETROSPECTIVE STUDY AT A distt headquarter hospital charsadda - Bangash, Nayella Nijat; Siddiqui, Naheed; Khan, Urooj Khushbakhat; Ullah, Ihsan; Nadeem , Faiza; Iqbal, Farzand (Journal of Rawalpindi Medical College, 2024)
Objective: To determine pattern and characteristics of medico-legal cases presenting to District Head Quarter Hospital Charsadda . Materials and methods: This retrospective study analyzed 500 patient records from the District Head Quarter Hospital Charsadda .It focused on various types of medicolegal cases (MLC), including firearm incidents, physical assault, poisoning, road traffic accidents, sexual assault, and sharp injuries. The study utilized a consecutive sampling technique and excluded cases with incomplete records, deceased individuals, and non-Pakistani nationals. Statistical analysis, including the Pearson Chi-Square test, was conducted to explore the patterns of MLC in relation to gender, age, and residence. Results: The mean age was 30.7±8.6 years. The females were 251(50.20%) while the males were 249(49.80%). The pattern of Medico-Legal Cases (MLC) is presented, highlighting both the frequency and percentage for each type. The most common was Road Traffic Accidents having 200(40%) followed by physical assault present in 104(20.80%). Sharp injuries were recorded in 95 cases, representing 19.00% of the total MLC. Poisoning cases were observed in 25 instances, constituting 5.00% of the total MLC. Sexual assault was reported in 56 cases, accounting for 11.20% of the total MLC. Firearm incidents accounted for 20(4%) of the total MLC. Among firearm incidents, 6.4% were female and 1.6% were males. For physical assault, 34% were female and 7.6% were male. Similarly, in poisoning and sexual assault cases, the percentages of females were higher compared to males. Sharp injuries had 26% female and 12% male. There significant association between gender and the MLC type (p<0.001). For firearm incidents, 5.6% occurred in rural areas and 2.4% in urban areas. A higher proportion of physical assault, poisoning, and sharp injuries cases were reported in urban areas. Road traffic accidents had a higher occurrence in urban areas compared to rural areas. These differences were highly significant (p=0.001). The distribution of incidents across different age groups did not show significant variation for any of the incident types (p=0.88) Conclusion: Road Traffic Accidents (RTAs) were the predominant type of Medico-Legal Cases (MLC), followed by physical assault and sharp injuries. Females were more commonly affected by physical assault, sexual assault, and poisoning, while males had a higher prevalence of RTAs.